La communication internationale : état des lieux et perspectives de recherche pour le XXIe siècle - Christian Agbobli (Communiquer)
The tradition of research in international communication has evolved over the past few years. From the importance of communication for development (a tradition that grew after the end of World War II), the field is now broken up into various objects (media coverage, information technology and communication, cultural diversity, etc.) and different geographical areas. The purpose of this article is to present an updated overview of research in international communication and to propose theoretical perspectives that need to be explored.